2014
DOI: 10.1021/cs5014442
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Catalytic Mechanism of Co3O4 for the Oxygen Evolution Reaction in a Li–O2 Battery

Abstract: Unraveling the catalytic mechanism of transition-metal oxides (TMOs) for the charging reaction in a Li−O 2 battery and characterizing their surface structures and electronic structure properties of active sites are of great importance for the development of an effective catalyst to improve low round-trip efficiency and power density. In the current study, an interfacial model is first constructed to study the decomposition reaction mechanism of Li 2 O 2 supported on Co 3 O 4 surfaces. The computational results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 73 publications
5
133
1
1
Order By: Relevance
“…[169,170] The high active catalyst should have an appropriate O adsorption strength close to those of well-established Pt and Pd catalysts. Other kinds of factors which can correlate with the performances, such as the catalyst size, [171,172] the crystal facet, [173,174] and the conductivity are reported. [175] Among these efforts, Zhu…”
Section: Correlation Between Electrocatalyst Property and Li-o 2 Battmentioning
confidence: 99%
“…[169,170] The high active catalyst should have an appropriate O adsorption strength close to those of well-established Pt and Pd catalysts. Other kinds of factors which can correlate with the performances, such as the catalyst size, [171,172] the crystal facet, [173,174] and the conductivity are reported. [175] Among these efforts, Zhu…”
Section: Correlation Between Electrocatalyst Property and Li-o 2 Battmentioning
confidence: 99%
“…Furthermore, they took surface acidity (defined as the energy change of catalysts with charge transfer) as a descriptor of charge transfer to study the electrocatalytic activity in the charging process [77,80,81]. They elucidated that the O-rich Co 3 O 4 (111) surface with a relatively low surface energy, promoting charge transfer from the Li 2 O 2 particles to the underlying surface, has a high catalytic activity to reduce overpotential and the O 2 evolution barrier [80]. Furthermore, as shown in Fig.…”
Section: Charge Transfermentioning
confidence: 99%
“…To examine the catalytic effect, Zhu et al carried out firstprinciples studies on the Co 3 O 4 surfaces and suggested that the Co 3 O 4 surface with Lewis acid sites is capable of reducing charge voltages due to facilitated electron transfer from Li 2 O 2 to the catalytic surface and a reduced O 2 desorption barrier. 141 Using a carbon-free, oxide-only cathode, moreover, Lee and his co-workers have provided clear evidence that Co 3 O 4 and other spinel-type transition metal oxides have the ability to catalyse O 2 reduction and Li 2 O 2 decomposition in an ether-based electrolyte. 142,143 Given that Li 2 O 2 should be stored within the cathode, three-dimensional (3D) architectures of the cathode would play a significant role in determining the electrochemical performance of non-aqueous Li-air batteries.…”
Section: View Article Onlinementioning
confidence: 99%